Care for Childbearing Women around the World during the COVID-19 Pandemic. Issue 3 (May 2021) - Callister, Lynn Clark
Abstract : Women and children in areas of the world with limited resources have many challenges accessing care during the COVID-19 pandemic. Our global health and nursing expert, Dr. Callister, highlights some of the global health organizations that are helping in these efforts.